2015
DOI: 10.1186/s13104-015-1191-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial profiles of markers of glycolysis, mitochondria, and proton pumps in a rat glioma suggest coordinated programming for proliferation

Abstract: BackgroundIn cancer cells in vitro, the glycolytic pathway and the mitochondrial tricarboxylic acid (TCA) cycle are programmed to produce more precursor molecules, and relatively less ATP, than in differentiated cells. We address the questions of whether and where these changes occur in vivo in glioblastomas grown from C6 cells in rat brain. These gliomas show some spatial organization, notably in the upregulation of membrane proton transporters near the rim.ResultsWe immunolabeled pairs of proteins (as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
3
2
0
Order By: Relevance
“…Our unexpected finding that the proliferating and invasive tumour periphery was more acidic than the hypoxic core agrees with a number of other studies (51,(63)(64)(65)(66). Low extracellular pH in tumours promotes invasion by increasing activity of low pHdependent enzymes that degrade the ECM, such as cysteine cathepsins (24,45), so it makes sense that the invading edge of a tumour should have a low pH e .…”
Section: Na V 15-induced Extracellular Acidification -A Positive Feed...supporting
confidence: 93%
See 1 more Smart Citation
“…Our unexpected finding that the proliferating and invasive tumour periphery was more acidic than the hypoxic core agrees with a number of other studies (51,(63)(64)(65)(66). Low extracellular pH in tumours promotes invasion by increasing activity of low pHdependent enzymes that degrade the ECM, such as cysteine cathepsins (24,45), so it makes sense that the invading edge of a tumour should have a low pH e .…”
Section: Na V 15-induced Extracellular Acidification -A Positive Feed...supporting
confidence: 93%
“…Our finding that the proliferating and invasive tumour periphery was more acidic than the hypoxic core agrees with a number of other studies (Helmlinger et al, 1997;Grillon et al, 2011;Grillon et al, 2015;White et al, 2017;Jardim-Perassi et al, 2019). Low extracellular pH in tumours promotes invasion by increasing activity of low pH-dependent enzymes that degrade the ECM, such as cysteine cathepsins (Gillet et al, 2009;Brisson et al, 2011).…”
Section: Functional Consequences Of Na V 15 Expressionsupporting
confidence: 91%
“…Translocase Of Outer Mitochondrial Membrane 20 (TOMM20) is a pre-protein receptor on the translocation complex of the mitochondrial outer membrane. According to previous studies, upregulation of TOMM20 could be observed in many cancers such as hepatocarcinoma [25][26][27][28]. However, the expression of TOMM20 was lower in GBM compared to normal samples in our study and it was highly expressed in low-risk group.…”
Section: Discussionsupporting
confidence: 47%
“…Thanks to previous studies, V-ATPase is known to be a key player in gliomagenesis, especially in isocitrate dehydrogenase 1 or 2 ( IDH1 or IDH2 ) wild-type gliomas [ 24 , 25 , 26 , 27 , 28 ]. Moreover, V-ATPase is supposed to participate in the drug resistance that characterizes high-grade gliomas, and it may be involved in the acidification of the glioma environment [ 26 , 29 ]. Finally, the expression of V-ATPase increases proportionally with the tumor’s grade [ 29 ].…”
Section: Introductionmentioning
confidence: 99%